Jinn and Hot Money: Morality and Cultural Risks in Bombana Gold Mining, Eastern Indonesia - Fitrilailah Mokui; Omar Pidani (Kawalu: Journal of Local Culture, 2019)
This study discusses the notion of Jin and Hot money as moral emblems to predict morality and public health risk in Bombana, gold mining areas. The result of this study indicates that good jinn control people to prevent from negative behavior and thinking. It means that good jinn contributes the positive consequences for both individual and community. On the other hand, the bad jin brings negative consequences. In addition, the morality standard for hot money and bad jinn are associated with risks condition and their impacts for individual as well as community.